The Effect of Firm Size, Profitability and Leverage on Corporate Social Responsibility (Case Study on Jakarta Islamic Index, 2016-2020) - Aristananda, Aristananda; Risman, Asep (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to analyze the effect of firm size, profitability (ROA) and leverage (DER) on corporate social responsibility. The population in this study are companies registered as members of the Jakarta Islamic Index in 2016-2020. Of the 30 listed companies, there are 11 companies that meet the criteria as samples in this study. Sampling was done by purposive sampling method, using panel data. The method of data collection was carried out using documentation techniques and library research techniques with data sources namely secondary data. The data analysis method uses statistical techniques through Eviews 9. This study proves that the size of the company has a negative and insignificant effect on the disclosure of corporate social responsibility. ROA has a significant negative effect on the disclosure of corporate social responsibility.